2014
DOI: 10.1021/ac503900w
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Hg2+ and MeHg+ in Aqueous Media with a Single Fluorescent Probe by Multiplexing in the Time Domain

Abstract: Development of a molecular probe for selective detection of MeHg(+) in the presence of Hg(2+) is a mission impossible to accomplish. Speciation analysis of two substrates with a single kinetic trace exploiting their differential reactivity toward a single probe, i.e., multiplexing in the time domain, is a cost-effective and powerful alternative. We have developed such a probe (Hg410) for simultaneously quantification of Hg(2+) and MeHg(+) in aqueous media. Hg410 is designed via the "covalent-assembly" approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…through in situ formation of fluorescent 7-N,N-dialkylamino-or 7hydroxy-(2-imino)coumarin or pyronin/rosamine scaffolds. 6,8,9 Further extension of the "covalent-assembly" principle to other less popular fluorescent molecules (e.g., benzo[c]cinnoline 10 , benzotriazole 11 , coumarin-fused resorufin) 12 , diazachrysene) 13 , phenantridine 14 and pyrazino-benz[e]indole derivatives 15 ) was also reported but the cascade reaction triggered by the analyte-ofinterest is often related to the specific reactivity of the latter and therefore not suitable for developing a versatile molecular chemosensing approach. Finally, some pioneering works have demonstrated that fluorescence biosensing at longer wavelengths (in the orange-red, far-red or near-infrared (NIR) spectral range) can be readily achieved through internal construction of polymethine dyes.…”
Section: Introductionmentioning
confidence: 99%
“…through in situ formation of fluorescent 7-N,N-dialkylamino-or 7hydroxy-(2-imino)coumarin or pyronin/rosamine scaffolds. 6,8,9 Further extension of the "covalent-assembly" principle to other less popular fluorescent molecules (e.g., benzo[c]cinnoline 10 , benzotriazole 11 , coumarin-fused resorufin) 12 , diazachrysene) 13 , phenantridine 14 and pyrazino-benz[e]indole derivatives 15 ) was also reported but the cascade reaction triggered by the analyte-ofinterest is often related to the specific reactivity of the latter and therefore not suitable for developing a versatile molecular chemosensing approach. Finally, some pioneering works have demonstrated that fluorescence biosensing at longer wavelengths (in the orange-red, far-red or near-infrared (NIR) spectral range) can be readily achieved through internal construction of polymethine dyes.…”
Section: Introductionmentioning
confidence: 99%
“…However, difficulty to discriminate the OrgHg species and its less applicability in complex matrix, the method become invalid at high cations concentration (like sea water samples), and yield false results in the presence of protein molecules (like in urine samples) are the main weaknesses of this technique. Zhang et al [85] proposed cost effective and powerful molecular probe for selective detection of MeHg in the presence of Hg 2+ and applied for their speciation analysis in aqueous media with a single kinetic trace exploiting their differential reactivity toward a single probe. Based on the strategy, low LODs, 0.0046 nM and 0.16 nM were reported for Hg 2+ and MeHg, respectively.…”
Section: Detection Techniquesmentioning
confidence: 99%
“…[38] There were no chemical probes nor dosimeters able to detect the speciation of Hg 21 and MeHg 1 when we started to work on the chemical sensors for mercury(II) species, and until recently, the development of a molecular probe for the selective detection of MeHg 1 in the presence of Hg 21 was considered a "mission impossible" to accomplish. [39] Hg 21 is a known thiophilic cation; therefore, the fastest way to develop chemical probes for the detection of Hg 21 is the complexation of Hg 21 by colorimetric or fluorogenic reagents having sulfur atoms. We have contributed some of these chromogenic probes from polysulfur-nitrogen heterocyclic compounds [40] or dithiolane oligomers.…”
Section: Discriminating Methyl Mercury(ii) From Mercury(ii) Cationmentioning
confidence: 99%
“…There are very few colorimetric or fluorogenic probes for MeHg + , which is in strong contrast to the enormous interest in the detection of MeHg + in living systems . There were no chemical probes nor dosimeters able to detect the speciation of Hg 2+ and MeHg + when we started to work on the chemical sensors for mercury(II) species, and until recently, the development of a molecular probe for the selective detection of MeHg + in the presence of Hg 2+ was considered a “mission impossible” to accomplish . Hg 2+ is a known thiophilic cation; therefore, the fastest way to develop chemical probes for the detection of Hg 2+ is the complexation of Hg 2+ by colorimetric or fluorogenic reagents having sulfur atoms.…”
Section: Discriminating Methyl Mercury(ii) From Mercury(ii) Cationmentioning
confidence: 99%